Herbs and roots : a history of Chinese doctors in the American medical marketplace - Shelton, Tamara Venit (Yale University Press, 2019)
An innovative, deeply researched history of Chinese medicine in America and the surprising interplay between Eastern and Western medical practice Chinese medicine has a long history in the United States, with written records dating back to the American colonial period. In this intricately crafted history, Tamara Venit Shelton chronicles the dynamic systems of knowledge, therapies, and materia medica crossing between China and the United States from the eighteenth century to the present. Chinese medicine, she argues, has played an important and often unacknowledged role in both facilitating and undermining the consolidation of medical authority among formally trained biomedical scientists in the United States. Practitioners of Chinese medicine, as racial embodiments of "irregular" medicine, became useful foils for Western physicians struggling to assert their superiority of practice. At the same time, Chinese doctors often embraced and successfully employed Orientalist stereotypes to sell their services to non-Chinese patients skeptical of modern biomedicine. What results is a story of racial constructions, immigration politics, cross-cultural medical history, and the lived experiences of Asian Americans in American history